MEMBANGUN STRATEGI PENGEMBANGAN SDM TRANSPORTASI UDARA - Sunarno; Solihin; Budi Prasetyo (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The development of transportation human resources requires a strategy that can maximize the potential of professional and competent human resources to support the implementation of national transportation system. This is done so that move the Wheels of national economy towards the realization of equiTabel distribution of sectoral development throughout Indonesia in accordance with national goals. This research method using qualitative analysis method to secondary and primary data in the form of HR data of Transportation and interview. The results 'of the study on Human Resource Development Strategy Transportation found that during the implementation of human resources development strategy has not been appropriate, so the availability of professional and competent human resources transportation has not been fulfilled in a sufficiently and flexible, evenly throughout the tenitory of the ground that affordable transpogation network both land, sea, air and rail. In the result of this study provide suggestions necessary to apply the Strategy of Human Resource Development proper so that the potential of human resources Transport is able to be distributed evenly through more comprehensive and sustainable human resources planning